The landscape fragmentation: analysis of land cover transformation in high mountains environment on the example of Tatra region (southern Poland) - Pyryt, Piotr; Pukowiec-Kurda, Katarzyna (Quaestiones Geographicae, 2024)
Changes in land cover (LC) are continuously growing due to natural and human factors, and they are even occurring within protected areas. In Europe, one such place is the Tatra region (southern Poland), which is the area of the presented research. Dynamic landscape transformation in a valuable natural area can negatively affect both environmental quality and sustainable land use planning. Appropriate recommendations and treatments can be introduced to prevent negative effects. To do this, it is necessary to understand the dynamics and character of these transformations. Therefore, the purpose of the article is to analyse changes in LC, its causes and their spatiotemporal dynamics, as well as the resulting landscape fragmentation. For this purpose, a set of landscape metrics and GIS (Geographic Information System) tools were used. The main data source in the study was the CORINE Land Cover (CLC) database. The results indicate a significant landscape transformation with a negative impact on the region’s environment, even in protected areas. Landscape fragmentation, which causes disturbances in ecosystems, increased across the entire study area. In turn, in the spatial development, it can introduce chaos and spatial disorder, and lead to the phenomenon of urban sprawl.